CRIME AND MISDEEDS AMONGST CERTAIN MEMBERS OF RAGUSAN COMMUNITIES IN MEDIEVAL SERBIA (1400 – 1459) (Heritage, 2024)
The goal of this paper was to review and analyze a certain number of crimes committed between Ragusans in medieval Serbia and thus gain some insight into history of crime as one of the aspects of everyday life as well as to draw some comparisons with criminality in the cities of medieval Italy. The analyzed cases date from the beginning of the 15th century up to 1459. The arrival of the Saxons into Serbia heralded a new era in the Serbian economy as the newly opened mines began to flourish. This newfound mineral wealth started to attract merchants in ever-increasing numbers from abroad, particularly Ragusa (Dubrovnik). These bustling Ragusan communities saw a great deal of strife while crime and violence were a part of everyday life. The motives of these crimes were usually financial gain or personal reasons such as rivalry. These cases were archived in the Ragusan archive because an independent judiciary was a privilege granted by charters of Serbian rulers. Some of the most common crimes were theft, burglary, robbery, physical violence, and insults. Oftentimes Ragusans served as customs officers on Serbian marketplaces and would misuse their position for financial gain at the great expense of their fellow Ragusans. Ragusans would also sometimes use Serbian or Ottoman authorities against their compatriots which was illegal as it was infringing upon Ragusan privileges. There are even records of Ragusan stealing each others ledgers and wills in an effort to erase evidence of their debts. The number of convictions of the crimes reported outside of Ragusa was quite low, at only about one quarter. Such a number would likely mean that the accuser and defendant would make peace without further interference from the court. There were probably many more cases that weren’t reported to court at all for the Ragusans would deal with them themselves if they considered that the best course of action. However, a certain level of trust in the judicial system was definitely present in the minds of the Ragusans of Serbia.
Keywords: Dubrovnik, Serbia, Middle Ages, medieval law, history of crime, cultural history